2018
DOI: 10.1155/2018/2845352
|View full text |Cite
|
Sign up to set email alerts
|

Rooming-in Reduces Salivary Cortisol Level of Newborn

Abstract: Background Rooming-in practice improves breastfeeding and reduces newborn stress reactivity. When this modality is not available, partial rooming-in after birth can be considered. Salivary cortisol levels (SCLs) are considered reliable biomarkers to indicate stress. Objective To test the hypothesis that rooming-in duration impacts neonatal stress response in hospitalized newborns. Design/methods Forty term newborns, enrolled in the Neonatology and Obstetrics Nursing, C.G. Ruesch, Naples, Italy, were divided, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Ultimately, this result made a further consideration of the device impossible for untargeted metabolomics analysis. Of note, the SOS device has been validated and used for the analyses of salivary analytes (e.g., cortisol, melatonin) (de Bernardo et al, 2018;Tapia et al, 2018), highlighting the significantly different analytical needs of targeted and untargeted LC-MS approaches. Finally, the Sugi device was characterized as the most robust and constant collection device tested with a reproducible volume recovery for all initial volumes tested (Rec % = 75.6%, with RSD = 6.1% for 0.2 mL), the lowest level of contaminants in both ESI+ and ESI-modes, as well as a significant and reproducible features recovery.…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…Ultimately, this result made a further consideration of the device impossible for untargeted metabolomics analysis. Of note, the SOS device has been validated and used for the analyses of salivary analytes (e.g., cortisol, melatonin) (de Bernardo et al, 2018;Tapia et al, 2018), highlighting the significantly different analytical needs of targeted and untargeted LC-MS approaches. Finally, the Sugi device was characterized as the most robust and constant collection device tested with a reproducible volume recovery for all initial volumes tested (Rec % = 75.6%, with RSD = 6.1% for 0.2 mL), the lowest level of contaminants in both ESI+ and ESI-modes, as well as a significant and reproducible features recovery.…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…Rooming-in and non-rooming-in issues had been scarcely investigated, previous studies comparing them focused on the neonatal and the breast feeding outcomes [4,12,13]. Therefore, the purpose of this study is to identify and compare difficulty in baby care activities and postpartum fatigue between women in rooming-in and non-rooming-in health care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the socioemotional stress reactivity during the early period of neonatal life would affected the brain development. 10,11 The part of the brain that had cognitive function was the cerebral cortex, but recent research showed that the cerebellum contained more neurons than the cerebral cortex that allowed it to be involved in cognitive function. 2 The cerebrum and cerebellum were interconnected through polysinaptics and form a system associated with cognitive function and interference neuropsychiatry.…”
Section: Introductionmentioning
confidence: 99%